Implementation of Risk Management in the Malaysian Construction Industry - Siang, Lee Chun; Ali, Azlan Shah (Journal of Surveying, Construction and Property, 2012)
Risk and uncertainty constantly plagued construction industry compared with other business activities due to its characteristics of complexity, dynamic and time consuming. As risk management is predicting the unpredictable, it is one of the most vital management tools to cope with project risks and uncertainties. Risk management is important to create values to a project and improve project performance in term of cost, time and quality. However, systematic risk management is not implemented in most of the existing construction companies in Malaysia. This situation leads to project failure such as cost overrun, schedule slip and poor quality performance. This article focuses on the implementation of risk management in Malaysian construction industry and attempt to establish the relationship between risk management and project performance. The data were obtained from desk works, followed by semi-structured interviews involved risk management personnel from 3 selected local construction companies. Findings concluded that risk management practices in Malaysian construction companies were relatively low and lack of standardisation. However, there were little evidence shows that project performance improved by implementing risk management exercise. Keywords: risk management; Malaysia; project performance